Challenges for Estimating the Global Prevalence of Micronutrient Deficiencies and Related Disease Burden: A Case Study of the Global Burden of Disease Study. Issue 12 (18th November 2021) - Hess, Sonja Y; McLain, Alexander C; Frongillo, Edward A; Afshin, Ashkan; Kassebaum, Nicholas J; Osendarp, Saskia J M; Atkin, Reed; Rawat, Rahul; Brown, Kenneth H
ABSTRACT: Information on the prevalence of micronutrient deficiencies is needed to determine related disease burden; underpin evidence-based advocacy; and design, deliver, and monitor safe, effective interventions. Assessing the global prevalence of deficiency requires a valid micronutrient status biomarker with an appropriate cutoff to define deficiency and relevant data from representative surveys across multiple locations and years. The Global Burden of Disease Study includes prevalence estimates for iodine, iron, zinc, and vitamin A deficiencies, for which recommended biomarkers and appropriate deficiency cutoffs exist. Because representative survey data are lacking, only retinol concentration is used to model vitamin A deficiency, and proxy indicators are used for the other micronutrients (goiter for iodine, hemoglobin for iron, and dietary food adequacy for zinc). Because of data limitations, complex statistical modeling is required to produce current estimates, relying on assumptions and proxies that likely understate the extent of micronutrient deficiencies and the consequent global health burden. Abstract : In this review, steps needed to estimate micronutrient deficiency prevalence and related disease burdens are described; challenges are outlined using the Global Burden of Disease Study as a case study.